Exploring the Type and Quality of Peer Feedback in a Graduate-Level Blended Course - Evrim Erbilgin; Jennifer M. Robinson; Adeeb M. Jarrah; Jason D. Johnson; Serigne M. Gningue (MDPI AG, 2023)
Most blended graduate courses engage students in peer feedback activities based on sociocultural theories of learning. Despite its growing importance, little is known about the quality and type of feedback that graduate students provide to their peers in online learning settings. This study aimed to explore the quality and type of feedback that graduate students provided to each other during online learning activities that took place in a blended course at a higher education institution in the United Arab Emirates. Volunteer students (n = 24) from four different sections of a graduate course were the participants of this study. The students' feedback to each other in two online discussion forums and in the final assessment paper were the data sources of this study. Qualitative data analysis methods were used to analyze the data. Based on the related literature, we analyzed the data from three perspectives: the type of feedback function (affirmation/negation, justification/explanation, praise, suggestion, question), the level of feedback (task, process, self-regulation), and the quality of each instance of feedback (ineffective, slightly effective, partly effective, effective) to investigate the nature of the peer feedback in detail. The data analysis indicated that graduate students might need support in providing high-quality feedback to their peers. The findings might help instructors improve the existing online or blended course designs.